2007
DOI: 10.1117/1.2804926
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive time-dependent cytometry monitoring by digital holography

Abstract: Using a digital holographic microscope setup, it is possible to measure dynamic volume changes in living cells. The cells were investigated time-dependently in transmission mode for different kinds of stimuli affecting their morphology. The measured phase shift was correlated to the cellular optical thickness, and then of the cell volume as well as the refractive index were calculated and interpreted. For the characterization of the digital holographic microscope setup, we have developed a transparent three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…The ability of QPI to differentiate between viable and non-viable cells without the use of staining has been extensively studied [21,83]. The first DH microscopy images of tumor spheroids were published in 2003 [84], and the first images of single cells one year after that [85].…”
Section: Cell Death Studies With Qpimentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of QPI to differentiate between viable and non-viable cells without the use of staining has been extensively studied [21,83]. The first DH microscopy images of tumor spheroids were published in 2003 [84], and the first images of single cells one year after that [85].…”
Section: Cell Death Studies With Qpimentioning
confidence: 99%
“…The first DH microscopy images of tumor spheroids were published in 2003 [84], and the first images of single cells one year after that [85]. Indeed, DH microscopy has turned out to be a very useful technique for cell death studies [21,83]. Cells that go into programmed cell death, or apoptosis, show a decreased cell phase shift as the first indication of early apoptosis, but several morphological alterations take place, such as cell shrinkage, formation of small blebs, nuclear fragmentation, chromatin condensation, chromosomal DNA fragmentation, and breakdown into several apoptotic bodies [86].…”
Section: Cell Death Studies With Qpimentioning
confidence: 99%
“…Among others, Kemper and coworkers have shown that erythrocyte shape can be clearly visualized by DHM . Kemmler and colleagues studied the morphological changes during trypsinization using oligodendrocytes from rat (Kemmler et al, 2007) and Emery and colleagues detected cell swelling and shrinking in primary mouse cortical neurons (Emery et al, 2007). Schnekenburger et al (2007) have applied DHM to study the dynamics of cytoskeleton changes in the human pancreatic tumor cell lines PaTu 8988S and PaTu 8988T.…”
Section: Cell Morphology Studiesmentioning
confidence: 99%
“…Using the refractive index to measure thickness, the study showed that cells treated with toxins or cell-death inducing drugs were thinner than control cells. DHM has also been used to follow the process of staurosporine-induced apoptosis in oligodendrocytes (Kemmler et al, 2007). More details of the apoptotic process have been shown by Colomb et al (2008), where the apoptotic blebbing in prostate cells was clearly visualized.…”
Section: Apoptosis Studiesmentioning
confidence: 99%
See 1 more Smart Citation